The association between sleep quality and well‑being amongst Allied Health Sciences Students in a public university in Malaysia - Mohd Zaid, Nurul Hazirah; A. Rahman, Nor Azlina; Haque, Mainul (Wolters Kluwer ‑ Medknow, 2018)
Background: According to researches, low sleep quality may lower the well‑being of the students directly. One of the known components of well‑being is satisfaction with life. Hence, this study is done to address if there is any relationship between sleep quality and well‑being by measuring the quality of sleep and satisfaction with life. Purpose: This study was done to identify the association between quality of sleep and well‑being amongst Allied Health Sciences students in a public university in Malaysia. Aside from that, it was also completed to compare the sleep quality and well‑being between the different study programs, years of study and genders of the students. Materials and Methods: The study design chosen for this study was a cross‑sectional study. A total of 120 students from the years 1, 2, 3 and 4 of the six study programs in the Allied Health Sciences faculty were selected by convenience sampling. The students were required to answer one set of questionnaires consisting of the consent form, information sheet, sociodemographic data, Pittsburgh Sleep Quality Index (PSQI) and Satisfaction with Life Scale (SWLS). The questionnaire was analysed by incorporating Kruskal–Wallis test, ANOVA, independent t‑test and Pearson correlation test. Results: This research found that there was no significant difference of PSQI and SWLS scores between different study programs (P = 0.250 and P = 0.106, respectively), years of study (P = 0.162 and P = 0.704, respectively) and genders (P = 0.070 and P = 0.201, respectively) in the faculty. The results, however, indicated that there was a significant fair negative correlation between PSQI and SWLS amongst the students (P < 0.001; r = −0.416). Conclusion: This study amongst Allied Health Sciences students can be safely concluded that there was no difference in sleep quality and satisfaction with life between audiology, dietetic, biomedical science, physiotherapy, optometry and radiography students, neither between the years 1, 2, 3 and 4 nor between male and female students. On the other hand, better sleep quality was significantly associated with better satisfaction of life, hence the well‑being of the students.